If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = x + 6 Reorder the terms: -3 + 4x = x + 6 Reorder the terms: -3 + 4x = 6 + x Solving -3 + 4x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 4x + -1x = 6 + x + -1x Combine like terms: 4x + -1x = 3x -3 + 3x = 6 + x + -1x Combine like terms: x + -1x = 0 -3 + 3x = 6 + 0 -3 + 3x = 6 Add '3' to each side of the equation. -3 + 3 + 3x = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 6 + 3 3x = 6 + 3 Combine like terms: 6 + 3 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| -2=-4x-6x | | 4(3r-2)=3(r+7) | | 7+3x=-22 | | 2-6-4= | | (8x-10)+(8x-10)=6x+6x | | a(-10)-8=-24 | | -3(2x-4)+4x=-34 | | w+(w+6)=334 | | (3r^2)-(10r)= | | 5n+5=10 | | 4x+32=88 | | 3x-3=180 | | 63=-9x | | x^2-21x-108=0 | | 14-.20(j-10)=.4(25+j) | | 3=3+5x+6x | | (3x+5)+2x=180 | | 2a-5=3a-15 | | 9b^2+15b-14=0 | | 42-r-2(13-5r)+7=85 | | 3x^2+90x=180 | | w+6=334 | | (x-5)-4(x-6)=9 | | 16x^4-5x^2-11=0 | | -3.2x=8.48 | | (1/8)(5y+64)=.25(20+2y) | | 3x=-2.25 | | 334=w(w+6) | | [36]/3= | | -1-15=-3t+t | | 2g=g+5 | | [36]3= |